The Struggles of Women Ad-Hoc Workers in General Elections amid Risks - Pratiwi, Oktafiani Catur; Sugiarto, Bowo (Salasika, 2025)
This study aims to elucidate the motivations and risks experienced by female poll workers (KPPS) who served at the village level during the 2019 general elections in Banyumas Regency. Researh on the motivations and risks of KPPS members, critical to the success of election, remains limited. Existing studies have primarily focused on the implementation of policies to ensure 30% political participation by women. Employing a qualitative approach, this study identifies three main motivations that encouraged women to join as KPPS members in Banyumas Regency. Firstly, their established track record and expertise in coordinating elections motivated their participation. Secondly, having a background as social activists served as a driving force for active engagement in the electoral process. Thirdly, close and patron-client relationships with the village heads and officials provide additional motivation. The female poll workers also faced three risks. Firstly, working in a patriarchal culture posed challenges, as it tended to restrict women’s employment opportunities in private sectors. Furthermore, there was a potential risk of assuming only a complementary role. Moreover, the patron-client political structure at the village level created vulnerabilities. A key finding of this study is that female KPPS members with a background in activism exhibit greater self-assurance in their participation compared to those primarily recruited through close and patron-client ties with village elites.